THE CONCEPT OF JUSTICE IN THE MANAGEMENT AND UTILIZATION OF NATURAL RESOURCES BASED ON THE 1960 BASIC AGRARIAN LAW - Fathoni, M. Yazid (Jurnal IUS (Kajian Hukum dan Keadilan), 2013)
The Agrarian Law of 1960 isÂ  basic rule for managing and exploiting natural resourcesÂ  in Indonesian which one itâs aim is to create justice to both state andÂ  citizen. Even though justice has beenÂ  established as itâs aim, but still the justice as stipulated in Agrarian Law of 1960 is unclear such as itâs definition, standing and position, function, as well as itâs profile and character. Such vagueness impacts on variety of things including the final purpose to which the law directs. Nevertheless, theoretically, the justice on the perspective of Agrarian Law of 1960 is relatively closer to utilitarianism theory has i.e. to create the happiness and welfare for the greatest number of Indonesian people. Finally, according to utilitarianism perspective, the happiness and welfare supposes to be enjoyed and possessedÂ  by every body, or if it canât be realized,Â  at least by the greatest number of people. Â Keywords: Natural Resources, Managing,Â  Justice